2022
DOI: 10.3390/brainsci12111424
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell and Platelet Counts Are Not Suitable as Biomarkers in the Differential Diagnostics of Dementia

Abstract: Apart from Alzheimer’s disease (AD), no biomarkers for the differential diagnosis of dementia have been established to date. Inflammatory processes contribute to the pathogenesis of dementia subtypes, e.g., AD or frontotemporal dementia (FTD). In the context of cancer or cardiovascular diseases, white blood cell (WBC) populations and platelet counts, as well as C-reactive protein (CRP), have emerged as biomarkers. Their clinical relevance in dementia, however, is currently only insufficiently investigated. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…A clinical study has indicated that MPV and PDW were abnormally decreased in VaD patients 43 . However, another study has reported insignificant variance in PLT between VaD patients and non‐dementia patients, indicating that PLT may not be a suitable biomarker for diagnosing VaD 44 . Accordingly, we conducted a MVMR study to explore whether MPV, PDW and PLT are confounding factors affecting the causal relationship between psoriasis vulgaris and VaD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study has indicated that MPV and PDW were abnormally decreased in VaD patients 43 . However, another study has reported insignificant variance in PLT between VaD patients and non‐dementia patients, indicating that PLT may not be a suitable biomarker for diagnosing VaD 44 . Accordingly, we conducted a MVMR study to explore whether MPV, PDW and PLT are confounding factors affecting the causal relationship between psoriasis vulgaris and VaD.…”
Section: Resultsmentioning
confidence: 99%
“…43 However, another study has reported insignificant variance in PLT between VaD patients and non-dementia patients, indicating that PLT may not be a suitable biomarker for diagnosing VaD. 44 Accordingly, we conducted a MVMR study to explore whether MPV, PDW and PLT are confounding factors affecting the causal relationship between psoriasis vulgaris and VaD. Following the LASSO feature selection, no significant collinearity was found in the MVMR analysis.…”
Section: Results Of the Mvmr Analysis Between Psoriasis Vulgaris Mpv ...mentioning
confidence: 99%
“…However, an elevated NLR has also been implicated in various other diseases and conditions, including those that are risk factors for AD, such as diabetes, hypertension, and obesity, raising questions as to whether the association with AD is simply a manifestation of underlying comorbidities (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Further, the shortcoming of the NLR as a tool for the differential diagnosis with other dementias, due to its lack of speci city, has recently been highlighted (51). Therefore, the need for an investigation into the NLR in speci c relation to Aβ and tau biomarkers, while accounting for comorbidities, has become apparent, particularly within the A/T/N framework.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PLT counts did not show statistically significant differences between dementia subtypes, this study recognised the evolving landscape of dementia diagnostics. Conducted using the Sysmex XN-10 Automated Haematology Analyzer, the research contributed to ongoing investigations of biomarkers in dementia diagnostics, highlighting the intricate nature of these conditions [118].…”
Section: Beura Et Al (2023) [109] Pdmentioning
confidence: 99%
“…Despite the rigorous methodology, the findings conclusively demonstrate that WBC counts, platelet counts, and related metrics do not exhibit significant differences across diverse dementia types. This underscores the urgent need for more reliable and specific biomarkers, both for accurate diagnostic differentiation and targeted treatment strategies [118].…”
Section: Platelets As Pivotal Players In the Tapestry Of Frontotempor...mentioning
confidence: 99%